Effects of Aqueous Ethanolic Leaf Extract of Boscia senegalensis (PERS) on Liver Function of Wister Strain Albino Rats (International Journal of Scientific Research and Management (IJSRM), 2014)
Boscia senegalensis has long been used as food, pesticide and medicine for the elimination of intestinal parasite from camel. The objective of this study was to evaluate the acute and sub acute toxicity (21 days) of Boscia senegalensis on the liver of Wister strain albino rats of both sexes via the oral route. For the acute toxicity, Boscia senegalensis extract was administered in a dose of 1000mg/Kg and 2000mg/Kg/day (n=3) while in the sub acute toxicity test, the following doses were administered; 100mg/Kg, 150mgKg, 200mg/Kg/day (n=5/group) for 21 consecutive days. In the acute toxicity test, Boscia senegalensis produce some toxic signs with no mortality. During the sub acute treatment with Boscia senegalensis, ALT was significantly high at P<0.001, AST was significantly high at P><0.05, while ALP was significantly high at P><0.01. However, Albumin and total protein were not significant at P>0.05. Therefore, the acute and sub acute administration of the aqueous ethanolic extract of Boscia senegalensis produced a toxic effect on Wister strain rats which is proven statistically to be dose dependent.